الملامح الرومانسية في شعر حامد حسن. - حسن, محمد معلا (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
ينتمي الشاعر حامد حسن إلى جيل من الشعراء، نشأ، وترعرع على قواعد المدرسة الكلاسيكية في الشعر العربي، كما واكب ألق الإبداع الرومنسي عند صفوة شعرائه، فتأثر بإبداع المدرستين، ومزج بين قيمهما الفنية، إلى درجة يصعب فيها تحديد موقعه منهما. تطمح هذه الدراسة إلى تسليط الضوء على الملامح الرومنسية في إبداع الشاعر، وذلك من خلال ما تحمله الصورة الفنية من الجدة والابتكار ، والعواطف الإنسانية الحارة ، وما تحمله اللغة الشعرية من العبارة الرشيقة ، والصياغة الأنيقة بمفرداتها ،وتراكيبها الهامسة خافتة النبرة ، والموسيقا الشعرية ،وما تحمله من غنائية عذبة ببعديها الداخلي والخارجي . الموسيقا الداخلية التي تصدر عن رقة الصياغة ، وانسجام اللفظ مع اللفظ .والموسيقا الخارجية المتمثلة بالوزن العروضي ، وإيقاع القافية ، وحرف الروي ، إضافة إلى الرؤية الفنية للواقع التي تجلت في إلغاء الواقع الموضوعي، والإتيان بواقع آخر، قد يكون خيالياً أو مثالياً ، أو قد يجمع الاثنين معاً ، وقد تجلى ذلك في قصائد رومانسية، تحدث بها عن الحب ، والمغامرات العاطفية . Hamed Hassan belongs to a generation of poets who grew up according to the conventions of Classicism in Arabic poetry. He was also a contemporary of the fascination of Romantic originality represented by its elite. He was, thus, influenced by the creativity of both schools, and he mixed their artistic values to an extent with which it became so hard to determine to which school he belonged. This study endeavors to shed light on the romantic features of the poet's creativity. This occurs through the artistic image which is serious and full of human emotions. In addition to that the poetic diction is characterized by unique coinage. Poetic musicality implies external as well as internal dimensions. The artistic vision which cannot be overlooked , appears clearly in the poet’s rejection of the existing reality and replacing it with another reality which can be fictious or ideal or both. All of this appears in his romantic poems which centre on love and emotional adventures